A Survey on Cases of Canine Transmissible Venereal Tumor (TVT) in Kintamani Dog - Claudia Murti Andari; I Made Kardena; I Ketut Puja (Veterinary Science and Medicine Journal, 2016)
The cases of canine transmissible venereal tumor (TVT) in Kintamani Bali Dog were studied by evaluating the cases in clinical records from some veterinary clinics in the two regencies of Badung, Gianyar and Denpasar City. A total of 486 clinical records on Kintamani Bali Dogs gathered from 2010 to 2014 was used in this study. Among those, the specific cases on TVT diagnostic were observed. The study showed that the prevalence of TVT was catagorised low. Three of Kintamani Bali Dogs were diagnosed  to have TVT (0.62%). Canine transmissible venereal tumor affected both male and female dogs. The tumor cases were recorded in varied ages,  from 2 to 5 years. This result indicates that TVT in Kintamani Bali Dogs is likely to be associated with the dog’s sexual maturity.